Evaluasi Kinerja Simpang Tiga Tak Bersinyal (Studi Kasus : Jl. Cemara – Jl. Cemara Asri Booulevard Raya) - Simanjuntak, Johan Oberlyn; Bartholomeus; Buulolo, Rizky M. (LPPM Universitas HKBP Nommensen, 2022)
Along with population growth and the magnitude of development as well as increasing transportation, the number of vehicles or traffic volume on roads is increasing, including one intersection in Deli Serdang Regency which has traffic density every day with concomitant congestion and a decrease in speed in certain road segments. This study aims to analyze the performance of the unsignalized intersection of Cemara Road – Cemara Asri Boulevard Raya Road and find alternatives to solve the problems that exist at the intersection of Cemara Road – Cemara Asri Boulevard Raya Road. The data collection method is carried out within a certain time by studying primary and secondary data. In this study resulted in the conclution that the intersection of Cemara Road – Cemara Asri Boulevard Raya Road experienced the peak of traffic flow on Sunday at 04.00 – 05.00 PM with a traffic volume of 2,782 smp/hour. The actual capacity is 2,451.6 smp/hour. The degree of saturation is 1.134. Based on value of the degree of saturation, the level of service at the intersection into category F exceeds the saturation limit suggested by the Indonesia Road Capacity Manual, which is > 1.00. It is necessary to revisit the three-arm intersection on Cemara Road – Cemara Asri Boulevard Raya Road. An alternative solution that can be given to obstacles found is the need for widening the geometric of the road in order to increase the capacity of the intersection and based on the degree saturation value, it is necessary to install the tools provided (lights traffic).